2014
DOI: 10.1186/1479-5876-12-92
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor is overexpressed in pancreatic cancer tissues and impairs insulin secretion function of β-cell

Abstract: BackgroundUnderstanding the pathogenic mechanism of pancreatic cancer associated diabetes (PCDM) might help yield biomarkers for the early diagnosis of pancreatic cancer (PC) from population with new-onset diabetes. In the current study, we sought to determine the role of macrophage migration inhibitory factor (MIF) in PCDM pathogenesis.MethodsThe protein and mRNA levels of MIF in paraffin-embedded human PC samples, chronic pancreatitis specimens, and normal pancreas were measured by immunohistochemistry and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 42 publications
3
37
0
Order By: Relevance
“…For example, a previous study demonstrated that in gastric cancer, positive MIF expression rates were 12, 52 and 96% in normal mucosal, gastritis and gastric cancer tissues, respectively (18). Similar observations have also been reported in pancreatic cancer, melanoma, hepatocellular carcinoma, malignant glioma and cervical adenocarcinoma (13,(19)(20)(21)(22).…”
Section: Mif and Carcinogenesissupporting
confidence: 72%
“…For example, a previous study demonstrated that in gastric cancer, positive MIF expression rates were 12, 52 and 96% in normal mucosal, gastritis and gastric cancer tissues, respectively (18). Similar observations have also been reported in pancreatic cancer, melanoma, hepatocellular carcinoma, malignant glioma and cervical adenocarcinoma (13,(19)(20)(21)(22).…”
Section: Mif and Carcinogenesissupporting
confidence: 72%
“…In the present study we used the pancreatic β ‐cell line HIT‐T15 to investigate the effects of canavanine on pancreatic cells, with the sulphonylurea glibenclamide used as a positive control. HIT‐T15 cells are a hamster‐derived insulin‐secreting cell line and the protein expression and exocytosis of this cell line are similar to those of islets . Glibenclamide is widely used to stimulate insulin secretion .…”
Section: Discussionmentioning
confidence: 99%
“…HIT-T15 cells are a hamster-derived insulin-secreting cell line and the protein expression and exocytosis of this cell line are similar to those of islets. 22 Glibenclamide is widely used to stimulate insulin secretion. 23,24 The findings of the present study indicate that HIT-T15 cells exposed to canavanine increased insulin secretion to a level similar to that induced by glibenclamide at the same concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The high efficient knockdown lentiviral constructs for MIF (pGIPZ‐shMIF‐1, shMIF‐2) and DDT (pGIPZ‐shDDT‐1 and pGIPZ‐shDDT‐2) were obtained from Open Biosystems (Rockford, IL). The third lentiviral construct for MIF or DDT knockdown (shMIF‐3 and shDDT‐3, respectively) was generated by using the shRNA design software from Dharmacon siDESIGN Center (http://www.dharmacon.com/sidesign/) as described previously . The oligos were 5′–TAATAGTTGATGTAGACCCGG–3′ for shMIF‐3 and 5′–GCCAGGACCGGATACTTAT–3′ for shDDT‐3.…”
Section: Methodsmentioning
confidence: 99%